Managing Cardiovascular Emergencies: Collaborative Approaches Involving Nursing, operations, Anesthesia, Public Health, and Health Administration - Mohammed Hamoud Essa Alqayd8, Raznah Abdullah Mahdi Alqahtani9, Norah Nasser Mohamed Alqahtani10, Haya Nasser Mohamed Alqahtani 11, Wafa Nasser Saeed Alshahrani12, Fahad Mohammed Y Al Dighrir1, Ahmed Hassan Ahmed Awad2, Ali Mohammed Ali Talbi3, Mohammed Hamoud Essa Alqayd4, Zakaria Yahua Hussin Najmi 5, Ahmed Hamed Hamoud Albanqah6, Ali Mohammed Ali Talbi7 (Journal of Population Therapeutics and Clinical Pharmacology, 2022)
Healthcare professional’s management of cardiovascular emergency situation in patient with critical illness is important to be analyzed. The multidisciplinary approaches across health care team and their collaboration can improve the quality of the management and reduce the complication that may occur. Cardiogenic shock, acute heart failure and myocardial infarction are from the life-threatening cardiovascular emergency issues that need a critical and instant intervention and management. Healthcare professional frequently encounter difficult clinical situations by selecting drugs based on comorbidities, the assessment of hemodynamics should be used to carefully guide treatment. Vasopressors, inotropes, and mechanical circulatory support are useful in some patients but are not always advised. In order to effectively manage cardiovascular emergency situations, early diagnosis, precise hemodynamic assessment, and timely therapeutic intervention are essential. In addition, healthcare providers should close the knowledge gap between evidence-based medicine and clinical practice.